Artificial Intelligence Marketing Capabilities And Competitive Advantage: The Mediating Role Of Customer Agility In The Digital Banking Sector - Utama, Satria Putra; Sudarmiatin, Sudarmiatin; Hermawan, Agus; Sari, Risca Kurnia (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
In the era of massive digital transformation, the banking sector faces immense pressure to adopt advanced technologies to maintain market relevance. This study aims to investigate the influence of Artificial Intelligence Marketing Capabilities (AIMC) on competitive advantage by positioning Customer Agility as a mediating variable in the context of the digital banking sector. Using a quantitative approach and Structural Equation Modeling (SEM) analysis, data were collected from marketing managers and decision-makers at a leading digital bank. The results show that AIMC significantly improves banks' ability to predict customer needs, which in turn strengthens customer agility. Furthermore, customer agility is shown to mediate the relationship between AI capabilities and competitive advantage, confirming that technology alone is insufficient without an organization's ability to respond quickly to changing customer behavior. These findings provide theoretical contributions to the Resource-Based View (RBV) and provide practical implications for banking management to prioritize investment in customer-oriented AI infrastructure to win the competition in a saturated market.